2017
DOI: 10.1016/j.colsurfa.2017.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic self-assembly of polysaccharides into nanofibers

Abstract: In this study, the anionic polysaccharide Xanthan gum (X) was mixed with positively charged Chitosan oligomers (ChO), and used as building blocks, to generate novel nanofibers by electrostatic self-assembly in aqueous conditions. Different concentrations, ionic strength and order of mixing of both components were tested and observed to affect the diameter, which ranged from 100 to 500 nm, and morphology of the self-assembled nanofibers. The release of diclofenac, as model drug, from self-assembled xanthan-chit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Shear rates showed significant difference only for CHT and KCA solutions, y-axis shows logarithmic scale; (b1, b2) representative light microscopic images of crosslinked fibrous and nonfibrous complexes resulted after bulk mixing of oppositely charged polysaccharide solutions. (c) Bulk mixing of oppositely charged polysaccharide solutions on a XY plate shaker leading to encapsulation of one of the solutions inside the electrostatically crosslinked membranous interface positively charged CHT oligomers (Mendes, Strohmenger, Goycoolea, & Chronakis, 2017). They studied the effect of order of addition of both solutions on electrostatically crosslinked capsule formation.…”
Section: Bulk Mixing Of Oppositely Charged Polysaccharides Failed Tmentioning
confidence: 99%
“…Shear rates showed significant difference only for CHT and KCA solutions, y-axis shows logarithmic scale; (b1, b2) representative light microscopic images of crosslinked fibrous and nonfibrous complexes resulted after bulk mixing of oppositely charged polysaccharide solutions. (c) Bulk mixing of oppositely charged polysaccharide solutions on a XY plate shaker leading to encapsulation of one of the solutions inside the electrostatically crosslinked membranous interface positively charged CHT oligomers (Mendes, Strohmenger, Goycoolea, & Chronakis, 2017). They studied the effect of order of addition of both solutions on electrostatically crosslinked capsule formation.…”
Section: Bulk Mixing Of Oppositely Charged Polysaccharides Failed Tmentioning
confidence: 99%
“…Chitosan (Ch) is a cationic polysaccharide consisting of N-acetyl glucosamine and glucosamine known for its biocompatibility, biodegradability, and mucoadhesivity [8] and ability to enhance gastrointestinal drug absorption [9]. Xanthan (X) gum is an anionic polysaccharide known for its peculiar physico-chemical properties [10] and has been used as encapsulating matrix [11]. A recent study from our group found that X-Ch-Cu nanofibers incubated with Caco-2 cells, resulted in enhancement of the in vitro absorption of Cu across cell monolayers, with a 3-fold increase of Cu permeability, compared to free-curcumin.…”
Section: Introductionmentioning
confidence: 99%
“…These water‐rich materials have been used as microcarriers in encapsulation of enzymes and bacteria ,[12] chemicals, in preparation of polyelectrolyte multilayers, and in other applications . Various inorganic‐ and bio‐chemicals have low solubility and low stability in aquatic environment but despite their water sensitivity they are of interest in numerous fields . The materials we reported here were made in waterless environment using both low and high concentration of xanthan and of chitosan.…”
Section: Resultsmentioning
confidence: 99%